Business Cycle Synchronization And Trade Intensity Between Indonesian And Some Of Main Trading Patners - B1011131044, feri diana siska (Jurnal Pembangunan dan Pemerataan, 2017)
ABSTRACT The globalization phenomenon has increased the intensity of trade. Theoretically, increasing theÂ  intensity of trade will improve the synchronization of business cycles. The purpose of this research first, to see the impact of the intensity of trade to the synchronization of the Indonesian business cycle. Secondly, it is to see the causalities between the trade intensity and business cycle synchronization during the period 1975 - 2014. The analytical method used is regression panel data to see the impact of trade intensity to the synchronizing Indonesian business cycle and vector autoregression (VAR) to see the causalities between the trade intensity and the synchronizing the Indonesian business cycle.The results of studies have shown, firstly that there is no influence on the trade intensity to the Indonesian business cycle synchronization with some trading partners such as Japan, Korea, Malaysia and Thailand. Secondly, there is a one-way relationship, where the intensity of trade affects business cycle synchronization. The implications of this study are important to have some appropriate macroeconomic policies related to the Indonesian trade relations with some of its major trading partners. Keywords : Trade Intensity, Business Cycle Synchronization